Determinant Analysis of Entrepreneurial Orientation in Business Organisations. - Bulky Maharsa; Abdul Rahman Kadir; Andi Nur Baumassepe (Hasanuddin Journal of Business Strategy, 2020)
The purpose of this study is to analyze the measurement of the entrepreneurial orientation (X) ​​derived from innovativeness, risk-taking, proactiveness, autonomy, and competitive aggressiveness factors. This research is explanatory research with quantitative methods. The population in this study were all food and beverage SME owners in Makassar City. The number of samples was determined as many as 99 respondents with a purposive sampling technique. The data collection method uses a questionnaire. The analytical tool used is partial Least Square (PLS). The results showed that entrepreneurial orientation was measured positively and significantly by Innovativeness. The best indicator for forming an innovativeness variable is X1.1 (focusing on product innovation rather than product/service marketing) because it has the highest loading value. Entrepreneurial orientation is measured positively and significantly by risk-taking. The best indicator forming the risk-taking variable is X2.1 (brave in taking new opportunities despite having a high risk) because it has the highest loading value. Entrepreneurial orientation is measured positively and significantly proactiveness. The best indicator forming the proactiveness variable is X3.2 (being the first compared to competitors in introducing new products and new services) because it has the highest loading value. Entrepreneurial orientation is measured autonomously positively and significantly. The best indicator [form the autonomy variable is X4.3 (has full power in determining the steps to run a business) because it has the highest loading value. Entrepreneurial orientation is measured by competitive aggressiveness in a positive and significant way. The best indicator forming the competitive aggressiveness variable is X5.2 (not afraid to face business competitors) because it has the highest loading value.